Coverage and Utilization in Food Fortification Programs: Critical and Neglected Areas of Evaluation. Issue 5 (12th April 2017) - Neufeld, Lynnette M; Baker, Shawn; Garrett, Greg S; Haddad, Lawrence
Abstract: The need for evidence to inform nutrition program design and implementation has long been recognized, yet the generation and use of evidence for program decision making has lagged. The results of the coverage surveys reported in this supplement highlight some of the strengths and areas for improvement of current population-based (i.e., staple foods and condiments) and targeted (e.g., foods for infants and young children) fortification programs. Among other topics, the results identify a few striking successful fortification programs whereby the majority of the food vehicle used is fortifiable and fortified, and coverage is equitable among those classified as vulnerable and not. Other programs have great potential based on very high use of a fortifiable food vehicle, including in most cases among the vulnerable, but that potential is not currently reached because of low compliance with fortification requirements. Programs were also identified whereby the food vehicle has limited potential to make public health contributions to micronutrient intake, given the low proportions of the population who consume the food vehicle in general or who consume the fortifiable food vehicle. Four key lessons were learned: 1 ) the potential for impact of food fortification depends on the appropriate choice of food fortification vehicle but also on the proportion of the food vehicle consumed that is fortifiable; 2 ) the design of fortification programs should be informed by the magnitude and distribution of inadequate intake and deficiency and consumption of fortifiable foods, and part of micronutrient deficiency control strategies to ensure coordination with other programs; 3 ) effective quality control of fortification levels in foods urgently needs strengthening, including the many governance and other policy factors that influence the capacity, resources, and commitment to do this; 4 ) periodic review of the assumptions related to dietary patterns that underpin food fortification is needed to ensure continual safe and impactful programs.